The Meta-Analysis of Innovative Mathematics Learning Toward the Mathematics Ability in Various Countries - Himmatul Ulya (AL-ISHLAH: Jurnal Pendidikan, 2024)
This meta-analysis examines the impact of innovative mathematics learning interventions on students' mathematical abilities across various countries and educational levels. The study aims to quantify the effectiveness of these interventions and highlight their relevance in diverse educational contexts. Research data were collected from Scopus-indexed articles published between 2018 and 2022. Following strict inclusion and coding criteria, 102 articles were initially identified, of which 81 articles with 82 independent studies were screened. After further refinement, 31 independent studies were included in the final analysis. Meta-analysis methods were used, with mean effect size values serving as the primary metric for evaluating the interventions' impact. The analysis yielded a summary effect size of 74.960, indicating a substantial positive impact of innovative mathematics learning interventions on students’ mathematical abilities. This effect was observed consistently across various educational levels and countries, underscoring the effectiveness of such strategies in enhancing mathematical proficiency. These findings underscore the critical role of innovative learning interventions in improving mathematics education globally. They provide empirical support for incorporating such strategies into curricula to address educational disparities and enhance learning outcomes. The study concludes that innovative mathematics learning interventions significantly improve students' mathematical abilities across diverse contexts. Further research is recommended to explore the long-term impacts and contextual factors influencing the efficacy of these interventions.